Improving Student Learning Outcomes On Theme 3 My Activities Through Media Power Point In Sd Negeri Sampang 01 - Astuti, Dahlia Ratna Kusuma (Universitas Sebelas Maret, 2020)
In the initial study of Tema 3 Kegiatanku, showed low interest and understanding of the material. If this is left it will have a negative impact on the next learning. To solve the problem, researchers made improvements to learning using power point media. Improvement of learning conducted by researchers aims to: (1) Improve the learning results of grade I students of Sampang State Elementary School 01 Sampang sub-district on the theme of 3 My Activities. (2) Applying media power points to improve the learning results of grade I students of Sampang State Elementary School 01 on the theme of 3 My Activities. Learning improvement research is carried out through two cycles, each cycle consisting of the stage of planning, performing actions, observing, and reflection. Cycle I was implemented on November 2 and 3, 2020 and cycle II was implemented on November 9 and 10, 2020. After the improvement of learning, the completeness of students' learning outcomes improved. In the initial study, of the 24 students who achieved completeness only 14 students (58.3%); after the first cycle, student learning results increased to 17 students (70.8%) who ate accomplished; after cycle II, completed study results reached 20 students (83.3%). Based on the data can be concluded that the use of power point media on the theme of 3 Kegiatanku can improve the learning results of grade I students of Sampang State Elementary School 01